Association between body mass index and survival in Taiwanese heart failure patients with and without diabetes mellitus. Issue 48 (3rd December 2021) - Lu, Yu Ying; Wu, Victor Chien Chia; Chu, Pao-Hsien; Ho, Chien-Te; Chang, Chieh-Yu
Abstract : Abstract: Body mass index (BMI) is positively associated with survival in heart failure (HF) patients with reduced ejection fraction (HFrEF). However, emerging evidence shows that this benefit may not exist in diabetic patients with HFrEF. As this relationship has not been investigated in Asian patients, the aim of this study was to examine the association between obesity and outcomes in HrEFF patients with and without diabetes mellitus (DM), and discuss the potential underlying mechanisms. The analysis included 900 patients with acute decompensated HF from the Taiwan Society of Cardiology-Heart Failure with Reduced Ejection Fraction Registry, of whom 408 had DM (45%). The association between BMI and all-cause mortality was examined using multivariate Cox proportional hazards regression after adjusting for covariates and Kaplan–Meier survival analysis. Echocardiography parameters were also analyzed in patients with different BMI and DM status. After adjusting for confounding factors, BMI was a significant independent predictive factor for all-cause mortality in the non-diabetic patients (hazard ratio [HR], 0.88; 95% confidence interval [CI], 0.81–0.95) and in Kaplan–Meier survival analysis (log-rank test, P  = .034). For diabetic patients, BMI was not a significant predictive factor for all-cause mortality (HR, 0.96; 95% CI, 0.90–1.02) and in Kaplan–Meier survival analysis (log-rank test P  = .169). Both DM (47.8 vs 45.4 mm, P  = .014) and higher BMI (48.6 vs 44.9 mm, P  < .001) are independently associated with higher left atrial size. Patients with a higher BMI had a lower proportion of severe mitral regurgitation (10.0% vs 14.1%, P  < .001). In non-diabetic patients with HFrEF, BMI was a significant predictor of survival. However, in diabetic patients with HF, BMI was not a significant predictor of survival. Diastolic dysfunction in patients with DM and obesity may have played a role in this finding.